2021
DOI: 10.4081/oncol.2021.544
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the search for germline pathogenic variants for breast cancer. How far should we go and how high should we jump? The missed opportunity!

Abstract: Since the identification of BRCA1 and BRCA2 genes 3 decades ago, genetic testing and genetic counseling have become an integral part of routine clinical practice. The risk of breast cancer among carriers of germline pathogenic variants, like BRCA1 and BRCA2, is well established. Risk-reducing interventions, including bilateral mastectomies and salpingo-oophorectomies are both effective and have become more acceptable. Many researchers and professional societies view current guidelines as restrictive and may mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…A criticism of providing MGPT for all patients with cancer is the wide variability in panel composition, which may lead to inclusion of moderate- and low-penetrance genes, 81 , 85 potentially limiting the clinical implications of including such genes for testing. However, published management guidelines for several moderate- and even low-penetrance cancer risk genes do exist.…”
Section: Innovating Implementation Strategiesmentioning
confidence: 99%
“…A criticism of providing MGPT for all patients with cancer is the wide variability in panel composition, which may lead to inclusion of moderate- and low-penetrance genes, 81 , 85 potentially limiting the clinical implications of including such genes for testing. However, published management guidelines for several moderate- and even low-penetrance cancer risk genes do exist.…”
Section: Innovating Implementation Strategiesmentioning
confidence: 99%
“…16 Several studies have performed cost modeling of expanding testing that accounts for appropriate screenings and risk-reducing interventions. 17 An analysis of population-based germline genetic testing of unselected women aged 50 years and younger in the United Kingdom and US using a panel comprising BRCA1/2, PALB2, RAD51C, RAD51D, and BRIP1 was found to reduce breast cancer incidence and was more cost-effective than a guideline-based strategy. 18 To fully assess the changes resulting from germline testing, it is vital to monitor treatment decisions and patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Jordan, as an upper-middle-income country, where 43–55% of all identified BRCA events are potential founder events, has a real opportunity to benefit of a customized BRCA screening panel to detect healthy carriers prior to costly disease treatment. Indeed, adopting such an early detection approach would certainly decrease the current estimated incidence of late diagnoses of breast cancer in the country, which makes ~ 12% of new cases (double the rate of developed countries) [ 15 ]. This is the first report highlighting the preponderance of BRCA1/2 founder variants in Jordan.…”
Section: Discussionmentioning
confidence: 99%
“…TP3 ) [ 14 ], and genetic testing and counseling have become an integral part of routine clinical practice. Nevertheless, many experts are continuously calling for expanding current testing guidelines both horizontally by including more patients and vertically by expanding the panel of genes tested for [ 15 , 16 ]. Mary-Claire King, who was the first to describe BRCA1 , has suggested that genetic screening, of at least BRCA1/2 , should be offered to every woman at around the age of 30 years, in order to detect healthy carriers prior to cancer onset [ 17 ].…”
Section: Introductionmentioning
confidence: 99%